White Sponge Nevus : Autosomal Dominant Genetic Disorder - Dwi Ariani; Pindobilowo (Formosa Journal of Applied Sciences, 2023)
Background: The oral cavity is an anatomically part of the body that has complex tissues and structures and is covered by soft, moist, and flexible non-keratinized mucosa for mobility. In some individuals, normal variations can be found, one of which is the White Sponge Nevus (WSN). These lesions are usually in the form of patches of white plaque that can be found by a dentist. Purpose: To identify and be able to differentiate normal variation lesions from pathological lesions that have similar clinical features. Method: Based on reference sources/references obtained from articles, journals for 2011-2021, textbooks, and websites accessed through the Google Scholar database, Science Direct, PubMed. Conclusion: In making a diagnosis, the dentist plays an important role in analyzing the etiology and predisposing factors in order to facilitate the identification of the White sponge nevus condition and eliminate other conditions which are a differential diagnosis. The normal variation of white sponge nevus has a good prognosis, so special medical treatment is not needed if it does not cause symptoms.